Label-free and Colorimetric Sensitive Detection of SNPs Based on Catalytic Beacon and RNase Cleavage Reaction - Yu, Zhaojiang; Zhao, Chunxue (Current Analytical Chemistry, 2023)
Background: Single nucleotide polymorphisms (SNPs) are important hallmarks in various pathological activities, especially genetic and inherited diseases, and detecting them with accuracy, high throughput and low cost becomes increasingly necessary.Methods: Herein, we have developed a new label-free and sensitive detection method for SNPs assay. Due to its favorable traits, the method presents an excellent performance. Briefly, the peroxidase- mimicking catalytic activity of G-quadruplex-hemin DNAzymes ensures label-free and colorimetric SNPs detection. At the same time, the RNA enzyme of the specific cleavage action can easily achieve the recycling of RNA enzyme and signal amplification.Results: In this study, the P-hemin DNAzyme with target DNA could catalyze the H2O2-mediated oxidation of ABTS to cause an observed color change compared to mutant DNA. The sensitivity and detection range of the DNA biosensor was achieved through the signal amplification program of special binding and cleavage of RNase H. A linear dependence of the absorbance at 420 nm on the concentrations between 0.5 and 50 nM was obtained (R2=0.965), and the detection limit was 8.76 nM.Conclusion: A new strategy for signal amplification process based on RNase cleavage reaction and Catalytic Beacon was constructed. Collectively, the developed SNPs assay might be extended to a broad range of clinical early diagnosis and treatment of genetic diseases.
Keywords: SNPs